Agricultural practices of the Qin people from the Warring States period to the Qin Dynasty: A case from the Matengkong site in Guanzhong Basin, China - Tang, Liya; Zhou, Hui; Wang, Zhiyou; Zhu, Jing; Liu, Jiaqi; Gao, Ziheng; Zhao, Zhijun (Frontiers in Ecology and Evolution, 2022)
In archaeological studies, the Qin people have often been a subject of research. The areas of investigation about the Qin include their origin, structure of tombs, funeral rites and interment processes, and cities and settlements. Although there are some studies on the Qin people’s diet which were conducted through isotope analyses, research on the agricultural system of the Qin people is still limited, especially during the period from the Qin people’s settlement in the Guanzhong Basin to the First Emperor bringing the seven states under his dominion. In the backdrop of the Warring States Period, it is necessary to investigate the nature of the Qin people’s agricultural economy and how it impacted their social progress. This study evaluates the Qin people’s agricultural practices based on flotation results from the Matengkong site, located southeast of the Guanzhong Basin in Shaanxi province. The results showed that the inhabitants practiced multi-cropping, and the crop assemblage comprised five categories, including dominant foxtail millet (Setaria italica) and wheat (Triticum aestivum), important broomcorn millet (Panicum miliaceum), less important soybean (Glycine max) and adzuki bean (Vigna angularis), less utilized barley (Hordeum vulgare), and cannabis (Cannabis sativa) and rice (Oryza sativa) of the lowest utilization. Wheat planting played a consistent and important role in agricultural production, and it appears to have had a high yield as same as foxtail millet. However, it appears to have contributed a small part of dietary intake. Rice does not appear to have been an important part of the Qin people’s subsistence at the site and there is no supporting evidence that rice was grown at Matengkong. Rather, it is possible that rice originated in Chu, a neighboring state to the south of Qin, through the ancient mountain passage. Adzuki bean, as a kind of crop resource, was widely used during the Zhou Dynasty. Moreover, Chenopodium sp. and Vitex negundo appear to have been intentionally used because of the high density in each single sample, but they might be multifunctional in nature.